German museum in Polish theatre? - Leyko, Małgorzata (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2015)
The paper concerns the influence of German drama and theatre on the theatre work in Poland after 1989. It is an attempt to capture the mechanism of this phenomenon and to test theoretical tools to describe and interpret it. Wolfgang Welsch’s concept of transculturality (1992) has been employed, with its assumption that homogeneity is a constitutive feature of neither the contemporary multicultural societies nor contemporary cultures any longer, and that the former formula of the whole has been replaced by the formula of differentiation. Taking into consideration Welsch’s thesis that contemporary cultures are characterised by blending and mutual permeation, selected examples were presented to illustrate the impact of German drama-theatre practice on Polish theatre: the dynamic development of the young drama, the ways of understanding national drama and the emergence of political theatre as a new phenomenon in the Polish tradition.